The Treaty of Versailles : A Very Short Introduction - Neiberg, Michael S. (New York Oxford University Press, 2019)
Signed on June 28, 1919 between Germany and the principal Allied powers, the Treaty of Versailles formally ended World War I. Problematic from the very beginning, even its contemporaries saw the treaty as a mediocre compromise, creating a precarious order in Europe and abroad and destined to fall short of ensuring lasting peace. At the time, observers read the treaty through competing lenses: a desire for peace after five years of disastrous war, demands for vengeance against Germany, the uncertain future of colonialism, and, most alarmingly, the emerging threat of Bolshevism. A century after its signing, we can look back at how those developments evolved through the twentieth century, evaluating the treaty and its consequences with unprecedented depth of perspective.
Include Illustrations and Index
Keywords: Peace -- World War, 1914-1918 -- Peace -- History